2017
DOI: 10.1007/s13205-017-0967-3
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of the herbicide paraquat by macromycetes isolated from southeastern Mexico

Abstract: Fifty-four macromycetes, isolated from southeastern Mexico, were used in order to evaluate their capacity for degradation and tolerance to the herbicide paraquat. Ten of these strains were capable of growing in a solid culture medium in the presence of 200 ppm paraquat. Subsequently, assays to evaluate the degradation of the xenobiotic in a liquid medium were carried out. Of the ten strains evaluated, three presented the highest levels of degradation of the compound, which were (54.2%), (54.1%) and They presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Biodegradation studies revealed that paraquat-degrading microorganisms do not exhibit similar efficiency in degrading different concentrations of paraquat. Camachomorales et al (2017b) isolated 54 macromycetes from southeastern Mexico, and only three ( Trametes pavonia ECS-67, Trametes versicolor ECS-79, and H. dispersum ECS-705) presented 54.2, 54.1, and 70.7% of paraquat (100 mg/L) degradation within 12 days. In another study Camachomorales et al (2017a) revealed that three other macromycetes including Polyporus tricholoma ECS-58 (32%, 75 mg/L), Cylindrobasidium laeve ECS-91 (26%, 25 mg/L), and Deconica citrispora ECS-77 (47%, 25 mg/L), showed lower paraquat degradation after 12 days of incubation.…”
Section: Microbial Degradation Of Paraquatmentioning
confidence: 99%
See 1 more Smart Citation
“…Biodegradation studies revealed that paraquat-degrading microorganisms do not exhibit similar efficiency in degrading different concentrations of paraquat. Camachomorales et al (2017b) isolated 54 macromycetes from southeastern Mexico, and only three ( Trametes pavonia ECS-67, Trametes versicolor ECS-79, and H. dispersum ECS-705) presented 54.2, 54.1, and 70.7% of paraquat (100 mg/L) degradation within 12 days. In another study Camachomorales et al (2017a) revealed that three other macromycetes including Polyporus tricholoma ECS-58 (32%, 75 mg/L), Cylindrobasidium laeve ECS-91 (26%, 25 mg/L), and Deconica citrispora ECS-77 (47%, 25 mg/L), showed lower paraquat degradation after 12 days of incubation.…”
Section: Microbial Degradation Of Paraquatmentioning
confidence: 99%
“…There is less information about the fungal degradation of paraquat, and the overall degradation effect of fungi is not as significant as that of bacteria. A recent study on fungi by Camachomorales et al (2017b) indicated that 70.7% paraquat was removed by Hypholoma dispersum ECS-705 in 12 days. Bacteria metabolize paraquat in two ways: (1) bacteria utilize paraquat as the sole nitrogen or carbon source, and (2) bacteria transform paraquat into low-toxic or non-toxic products through co-metabolism.…”
Section: Bioremediation Potential Of Paraquat-degrading Microorganismsmentioning
confidence: 99%
“…It has been established that a number of fungus species are effective paraquat degraders. For instance, T. versicolor ECS-79, T. pavonia ECS-67, and H. dispersum ECS-705 can degrade paraquat at similar 55, 55, and 71% rates, respectively (Camachomorales et al, 2017). Funderburk (1969) found that L. starkeyi was able to degrade both Diquat and paraquat.…”
Section: Introductionmentioning
confidence: 99%
“…The degradation capacity by macromycete fungi was also reported by Camacho‐Morales et al . (2017). They found that Tremates pavonia , Trametes versicolor and Hypholoma dispersum isolated from soils in Mexico exhibited high capacity in paraquat degradation (54–70%).…”
Section: Introductionmentioning
confidence: 99%